2017
DOI: 10.1017/s0021859617000727
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of yield and quality in winter rapeseed (Brassica napus L.) under Mediterranean conditions

Abstract: SUMMARYWinter rapeseed was introduced into Greece a decade ago to provide oil for biodiesel. To identify agronomic traits affecting yield and quality, three hybrids and an inbred line were tested over two seasons (2005–2006 and 2006–2007) and four locations, in central and northern Greece, varying in pedo-climatic conditions. The large variations in seed yield, quality and agronomic traits were largely ascribed to location; in contrast, cultivar accounted for ⩽0·010 of the variation for many traits. Below 40°N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…However, earlier traits used as essential yield components for seed production per plants such as pod length (Zhang et al, 2010), seed weight per pod (Yang et al, 2012), number of seeds per pod (Chay & Thurling, 1989), and 1000‐seed weight were not significantly correlated with seed yield per plant of B. napus (Bennett et al, 2017). It is noteworthy that the studied traits (i.e., number of seeds, branches, and siliques per plant, and 1000‐seed weight) were not correlated to seed yield (g m −2 ) of camelina (Table S1), similarly to previous results on B. napus (Tsialtas et al, 2017). Contrarily, the results of Berti et al (2011) on camelina indicated that the siliques number per plant and 1000‐seed weight are the leading yield components related positively with seed yield of camelina.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, earlier traits used as essential yield components for seed production per plants such as pod length (Zhang et al, 2010), seed weight per pod (Yang et al, 2012), number of seeds per pod (Chay & Thurling, 1989), and 1000‐seed weight were not significantly correlated with seed yield per plant of B. napus (Bennett et al, 2017). It is noteworthy that the studied traits (i.e., number of seeds, branches, and siliques per plant, and 1000‐seed weight) were not correlated to seed yield (g m −2 ) of camelina (Table S1), similarly to previous results on B. napus (Tsialtas et al, 2017). Contrarily, the results of Berti et al (2011) on camelina indicated that the siliques number per plant and 1000‐seed weight are the leading yield components related positively with seed yield of camelina.…”
Section: Discussionsupporting
confidence: 88%
“…Contrarily, the results of Berti et al (2011) on camelina indicated that the siliques number per plant and 1000‐seed weight are the leading yield components related positively with seed yield of camelina. The present work showed no correlation between seed yield and plant height as reported by Tsialtas et al (2017). The reason of obtaining this result is not clear but it may have something to do with the plasticity of the yield parameter in the camelina, as previously proposed by Urbaniak et al (2008), McVay and Khan (2011), and Gesch et al (2018), who repeatedly reported that the seed yield (g m −2 ) is little affected over a large range of plant densities because of its yield plasticity.…”
Section: Discussionsupporting
confidence: 51%
“…Breeders and agronomists have a significant challenges in developing new varieties with more reliable yields and quality features. To do this, we must uncover and evaluate data from multi-environment studies that previously had been buried (Tsialtas et al, 2017). Sunflower may become the preferred oilseed crop due to global environmental changes and its capacity to thrive in various agro-ecological situations, including mild drought.…”
Section: Introductionmentioning
confidence: 99%
“…The oilseed rape crop, which we studied in the present paper, is considered a strong rooting-break species and an improver of soil structure [32,33]. For this last reason, in Mediterranean environments, it is commonly grown in an annual rotation with winter cereals [32,34,35], thus minimizing the risk to cause the selection of herbicide-weed resistance when herbicides are applied at reduced doses.…”
Section: Introductionmentioning
confidence: 99%